Penetapan Kadar Fenolik Total Ekstrak Daun Jotang (Sphagneticola Trilobata) Dengan Spektrofotometri UV-Vis - Ghalib Syukrillah Syahputra; Delladari Mayefis; Tommy Julianto; Lyna Elvira (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Phenolic compounds are the largest group of compounds that act as natural antioxidants in plants. One of the plants that has the potential as a natural antioxidant is Jotang (Sphagneticola trilobata). This study aims to determine whether jotang leaf extract (Sphagneticola trilobata) has phenolic content and to determine the total phenolic content in jotang leaf extract (Sphagneticola trilobata). Jotang leaves were extracted by maceration method using methanol solvent. The method of determining total phenolic content was carried out using Folin-ciocaltaeu reagent because phenolic compounds can react with Folin-Ciocalteu to form a solution that can be measured absorbance. As a standard solution, gallic acid is used which is reacted with Folin-Ciocalteau reagent to produce a yellow color indicating that it contains phenolics, after which it is added with Na₂CO₃ solution as a base atmosphere giver. The phytochemical screening of jotang leaf extract showed positive results containing flavonoids, alkaloids, saponins, phenolic compounds, and triterpenoids. Determination of the wavelength of gallic acid obtained maximum 653 nm. The results showed that jotang leaf extract (Sphagneticola trilobata) has phenolic content and obtained total phenolic content of jotang leaf extract of 0.909 mg /g.